Organoleptic Test On Some Flour Substitutions As A Basic Alternative Selection of Functional Cookies Flour For Patients With Type 2 Diabetes - Anita Wulandari; Wahyu Kanti Dwi Cahyani (Faculty of Agriculture, Merdeka University Surabaya, 2019)
Diabetes Mellitus (DM) became the biggest problems common in developed and developing countries including Indonesia. Estimates WHO that in 2025, Indonesia will be ranked 5th in the world. The triggering factors for DM are unhealthy and proper eating patterns. Snack is a habit of Indonesian people, namely snacking on food to accompany all their activities. One snack that is commonly consumed is cookies. Cookies are made from the main ingredient of wheat flour and supporting raw materials. The purpose of this study: 1) Conducting sensory tests to determine the level of consumer preferences on cookies brown rice, corn, soybeans, purple yam, and basil; 2) Obtain formulations on all types of flour that are suitable for making cookies. The research will be carried out at University 17 August 1945 Surabaya Laboratory. The organoleptic test analysis method uses excel analysis. The analysis carried out consisted of sensory analysis and proximate analysis. The results of sensory analysis of cookies favored by consumers starting from taste are in the control treatment, A2, B2 and C1. The color of cookies favored by consumers are control, A4, B1, B2, B3, C1, C2, C4, and D2. Aroma cookies preferred by consumers are control, A2, B1, B2, B3, C1, and C3. The cookies that are preferred by consumers are control, A2 and B1. While cookies that are not preferred by consumers in terms of taste are A4, B4, C3, D1, E1, E2, E3, and E4, the colors are D3, D4, E1, E2, E3, and E4, the aroma is treatment B4, D3 , D4, E1, E2, E3, and E4, and the impression in the mouth is the treatment of B4, C2, C4, D3, D4, E1, E2, E3, and E4.